Risk factors for overall survival outcome in surgically treated human papillomavirus-negative and positive patients with oropharyngeal cancer - Würdemann, Nora; Prigge, Elena-Sophie; Reuschenbach, Miriam (Oncology research and treatment, 2017)
Introduction: This study reports the oncological outcome of a non-selected series of patients with human papillomavirus(HPV)-positive and -negative oropharyngeal squamous cell carcinoma (OSCC) preferentially managed with upfront surgery. Methods: Consecutive OSCC cases (n = 378) diagnosed from 2000 to 2010 in our department were evaluated for risk factors, HPV association, therapy and overall survival (OS). HPV status was determined by combined DNA and p16 testing, and treatment was defined as the first course of treatment with any kind of surgery (upfront surgery) or primary chemoradiotherapy. OS of HPV-associated and HPV-negative patients was compared using Kaplan-Meier and multivariable Cox regression analyses. Results: The majority of OSCC patients (215 of 361; 69.5%) received upfront surgery as first-line treatment in curative intent. The 5-year OS rate in patients with HPV-positive and HPV-negative tumors were 81.1 and 39.7%, respectively. Upfront surgery in HPV-negative (p < 0.001) and HPV-positive patients (p = 0.05) resulted in improved OS only in advanced stages. Multivariate analysis for patients revealed age in HPV-associated OSCC as an independent predictor for improved survival, and age, performance, N status and therapy as independent predictors in HPV-negative OSCC. Conclusions: Non-selected OSCC patients amenable to curative therapy show poor 5-year OS. The benefit of upfront surgery remains unclear. A younger patient age was the main factor for a better outcome in patients with HPV-associated OSCC.